ChemInform Abstract: Nanosized Rare‐Earth Hexaborides: Low‐Temperature Preparation and Microstructural Analysis. Issue 37 (22nd August 2013) - Aprea, Alessia; Maspero, Angelo; Masciocchi, Norberto; Guagliardi, Antonietta; Albisetti, Alessandro Figini; Giunchi, Giovanni
Abstract Rare earth hexaborides LnB6 (Ln: Ce, Nd, Sm, Eu, Gd, Yb) are prepared from mixtures of LnCl3·6H2O and MgB2 (650 °C, 1 h).